Auto FILL Fluid using Arduino (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The research presents an automated bottle-filling system through a control system, where the system contains the main control unit, which is the Arduino, through which, and through its programming, we control all the instructions in light of the programming and the servo motor through which the mechanical part that is mounted on it rotates and will contain the bottles. It also contains a small keyboard through which any instructions can be given for the purpose of filling bottles. It also contains a water pump through which we perform the automatic flow of water as needed. It also contains a relay that operates the water pump and is equipped with a power of 5-7 volts.This process can be used for health prevention without direct human intervention to prevent transmissible diseases that can be in the form of viruses or bacteria concentrated on the surfaces of objects. We can also develop this work and have it via the Internet, which we will talk about in the proposals in the coming chapters to develop the project.